Circular Migration. Identity Treks of the Lemkos: Text and Ritual - Duć-Fajfer, Helena (Porównania, 2022)
The total, two-stage resettlement of the Lemkos in 1945–46 and 1947 was the point of departure for their migration/diaspora identity. Consequently, the settled, native community that had established its identity upon a territorial determinant became a community dispersed over several diaspora territories. Therefore, a crucial identity reinvention had to take place, constructed upon the migration determinant. The purpose of this paper is to capture the essence of the reinventive myth of a ritual dimension—the cyclic rituals of traveling between the lands of expulsion and the Carpathian motherland, and the textual dimension—providing meaning and symbolic value to these treks. The empirical, material basis for the research is provided by cultural texts, mainly Lemko writings from recent decades, as well as data from participant observation and field studies carried out by the author in 2017 in three areas currently inhabited by the Lemkos and considerably distant from one another.